2007
DOI: 10.1111/j.1743-7563.2007.00114.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of distress in cancer patients undergoing chemotherapy

Abstract: Aim: Feeling distressed is often a normal reaction to the diagnosis of cancer and cancer treatment. However, if excessive, distress may lead to more disabling conditions such as depression and anxiety. The aims of the study were to determine the prevalence and level of distress in patients with cancer who were undergoing chemotherapy and to examine the associated factors related to psychological distress in these patients. Methods: Adult patients with confirmed cancer who were undergoing out-patient chemothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 21 publications
1
18
2
1
Order By: Relevance
“…Lim observed that cancer patients might present with adjustment disorder, which is still a clinically significant response to cancer. Zainal et al . and Koo et al .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Lim observed that cancer patients might present with adjustment disorder, which is still a clinically significant response to cancer. Zainal et al . and Koo et al .…”
Section: Discussionmentioning
confidence: 96%
“…The distress thermometer has been validated, against the hospital and anxiety depression scale (HADS), General Health Questionnaire‐12 and Brief Symptom Inventory‐18 in America, in Japan and in Italy, Portugal, Spain and Switzerland . A previous study in Malaysia did use the distress thermometer as a screening tool, but did not validate the instrument . Mitchell et al .…”
Section: Introductionmentioning
confidence: 99%
“…Both post-surgery and chemotherapy are known to precipitate psychological distress, anxiety or depression. Postsurgery breast cancer may lead to body image distress and chemotherapy agents may cause toxic side effects such as vomiting, fatigue, hair loss, etc (Zainal, 2012). Breast-Impact Treatment Scale (BITS) is a self-report questionnaire to measure the body image distress experienced by breast cancer patients after breast surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[11] As seen in different researches conducted, distress, which is a multidimensional symptom, is seen in individuals diagnosed with cancer at varying rates. [9][10][11][12][13] Furthermore, there are many researches made proving that there are problems that exist causing individuals to experience distress in physical, social, and spiritual areas of life. [14][15][16][17][18][19][20][21][22] Thus, the problems experienced by individuals diagnosed with cancer and distress that occur as a result of these problems should be handled together.…”
Section: Data Collection Toolsmentioning
confidence: 99%
“…[9] In a research made by Liao and his friends (2015) over 97 individuals diagnosed with cancer, it was stated that all of the patients experienced distress at intermediate level and that the level of distress had increased dur-…”
Section: Introductionmentioning
confidence: 99%